2015
DOI: 10.1074/jbc.m115.671982
|View full text |Cite
|
Sign up to set email alerts
|

Human MageB2 Protein Expression Enhances E2F Transcriptional Activity, Cell Proliferation, and Resistance to Ribotoxic Stress

Abstract: Background: MageB2 is a tumor-specific antigen with unknown function. Results: Through a mechanism involving histone deacetylases, MageB2 enhances E2F activity and resistance to Actinomycin D. Conclusion: MageB2 is a protein conferring proliferation properties and resistance to ribotoxic stress to tumor cells. Significance: Expression of MageB2 in human tumors could be a marker of chemotherapy refraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Among the 38 genes exclusively expressed in SKOV-3 cells (Supplementary Table S2), ALDH1A1 [26], GABRA3 [27], FOLR1 [28], DPYSL5 [29], CGB8 [30], C8orf4 [31] and MAGEB2 [32] could be intriguing for the development and maintenance of the neoplastic phenotype. Similarly, among the 82 genes expressed only in FT194 cells (Supplementary Table S2) CDKN2A [33], MT1G [34], GPX7 [35], HCK [36], ZBTB16 [37] could be looked at as interesting genes being tumor suppressor epigenetically silenced in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 38 genes exclusively expressed in SKOV-3 cells (Supplementary Table S2), ALDH1A1 [26], GABRA3 [27], FOLR1 [28], DPYSL5 [29], CGB8 [30], C8orf4 [31] and MAGEB2 [32] could be intriguing for the development and maintenance of the neoplastic phenotype. Similarly, among the 82 genes expressed only in FT194 cells (Supplementary Table S2) CDKN2A [33], MT1G [34], GPX7 [35], HCK [36], ZBTB16 [37] could be looked at as interesting genes being tumor suppressor epigenetically silenced in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work by Peche et al also showed that MAGE-B2 interacts with HDAC1, an E2F1 repressor, to enhance E2F1 transactivation [60]. Therefore, whereas some type II MAGEs target and inhibit E2F function, other type I MAGEs may stimulate E2F activity to promote tumor cell proliferation.…”
Section: Function and Mechansim Of Mage-ring Ligasesmentioning
confidence: 99%
“…For example, knockdown of mouse Mage-b genes reduces cell viability in melanoma and mast cell lines [37, 155]. Similarly, MAGE-B2 promotes cell proliferation in transformed oral keratinocytes, osteosarcoma, and colon cancer cell lines [60, 151]. Moreover, Mage-b knockdown suppresses growth in a syngeneic mouse model, whereas over-expression of MAGE-B2 enhances tumor growth in mice [37, 60].…”
Section: Mages In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, BORIS/CTCFL up-regulates h-TERT (62), and through poorly defined mechanisms inhibits apoptosis in cancer cells (63). MAGE-A11 inhibits function of the RBL1/ p107 tumor suppressor (64), and MAGE-B2 enhances E2F activity to promote cell cycle progression (65). MAGE-A2, and MAGE-C2 impair p53 function by directly inhibiting binding of p53 to target promoters, promoting deacetylation (inactivation) of p53, or by enhancing ubiquitin-mediated degradation of this tumor suppressor (66-68).…”
Section: Loss Of Imprinting (Loi) and De-repression Of Cg Genesmentioning
confidence: 99%